Polycrystalline-silicon-based double-gate ion-sensitive field-effect transistors using APTES/SiO2 stack-sensing membrane. (1st June 2022) - Chen, Jun-Rong; Chen, Henry J. H.; Tseng, Shin-Lun
Abstract: This study demonstrated a polycrystalline-silicon (poly-Si)-based double-gate (DG) ion-sensitive field-effect transistors (DG-ISFETs) using APTES/SiO2 stack-sensing membrane. The APTES/SiO2 stack-sensing membrane enhanced the single-gate (SG) sensitivity, and suppressed the hysteresis. The DG structure was preferred to have a capacitive coupling effect and to amplify the sensitivity of ISFETs. The sensitivities of SG- and DG-ISFETs were approximately 56.8 and 294 mV pH −1, respectively. In addition, the corresponding amplifying factor was approximately 5.2. With this approach, the poly-Si DG-ISFETs can be a candidate for future high-performance biochemical sensing applications.